Experimental study and optimization of a combustion-based micro thermoelectric generator. (25th November 2020) - Wang, Wei; Zhao, Zhengyang; Kuang, Nianling; Chen, Huiyan; Liu, Jinxiang; Zuo, Zhengxing
Highlights: A combustion based micro-thermoelectric generator was prototyped and tested. The maximum total efficiency of 3.34% was obtained by experimental method. The variation of η th with Qin is opposite to η TE in the working range of TE module. The maximum η TEG of 4.22% is obtained with optimization of the H and N. Abstract: Thermoelectric generator (TEG) has drawn extensive attention for the power supply in various portable electronic products. This work developed a prototype of a combustion based micro-TEG, composed of micro combustor with high uniform surface temperature and wide flame stability range, thermoelectric (TE) module and water cooling heat sink. The effects of input fuel energy, equivalence ratio and hydrogen addition on the output power are tested. An energy balance analysis is conducted based on the experiment results. The results show that the lowest thermal efficiency exceeds 79%, which confirms the high efficiency of the micro combustor. A maximum total efficiency of 3.34% is obtained with input fuel power of 109 W and load resistance matching the internal resistance of TE module. An analytical model of the micro-TEG was developed and validated. Three kinds of TE materials are employed and the simulation results are compared. The effects of length and number of the TE leg on the total efficiency under different input fuel conditions are analyzed. A maximum total efficiency of 4.22% is obtained with optimization of the TE module structure. The heat loss through the gap between TE legs reduces the maximum total efficiency for lower length of the TE leg. This work deeply explains the interaction between the micro combustor and TE module, which gives valuable guideline for the optimization of the micro-TEG.